PENENTUAN KADAR LOGAM TIMBAL (Pb) AIR SUNGAI SINGINGI DI KABUPATEN KUANTAN SINGINGI RIAU - Putri Ade Rahma Yulis (UIR Press, 2019)
Heavy metal is the most hazardous of contaminats group. Our ecosystem has been contaminated by high concentrated of heavy metal that was generated from human activities such as industrial. On this research heavy metal content due to illegal gold mining (PETI) activities in Singingi river, Riau was measured. This was held because the river has degradation of its quality immediately. It was marked by high turbidity and declining of organism in that river. The choice of determining the content of heavy metal Pb or lead because we know that gold processing is not only used by mercury but also used by lead and cadmium to bind gold. The three metals are used to bind the gold and separate it from soil and stone in from sulfide.. This research used survey method with purposive sampling based on the rise location of PETI activities. Sample was measured at 4 point that started from the nearest and up to the furthest of PETI activities. The result of lead measurement was 0, 00382 mg/L; 0,00165 mg/L; 0,00124 mg/L and 0,02525 mg/L, respectively. The results obtained indicate that the river has been contaminated with lead metal although if were compared with the quality standard of heavy metal in aquatic Lead still allowed with the number of quality standard for lead is 0,03 mg/L. Keywords : PETI activities, heavy metal measurement, Lead (Pb) Singingi river